Gap junctions in the cardiovascular and immune systems - Rozental,R. (2000)
Gap junctions are clusters of intercellular channels directly connecting the cytoplasm of adjacent cells. These channels are formed by proteins named connexins and are present in all metazoan organisms where they serve diverse functions ranging from control of cell growth and differentiation to electric conduction in excitable tissues. In this overview we describe the presence of connexins in the cardiovascular and lympho-hematopoietic systems giving the reader a summary of the topics to be covered throughout this edition and a historical perspective of the discovery of gap junctions in the immune system.